Streptococcus pneumoniae Endopeptidase O Promotes the Clearance of Staphylococcus aureus and Streptococcus pneumoniae via SH2 Domain-Containing Inositol Phosphatase 1-Mediated Complement Receptor 3 Upregulation - Li, Sijie; Zhang, Hong; Xiao, Jiangming; Yuan, Taixian; Shu, Zhaoche; Min, Yajun; Xu, Wenchun; Yin, Yibing; Zhang, Xuemei (Frontiers in Cellular and Infection Microbiology, 2020)
Increasing evidences demonstrate that microorganism and their products protect against bacterial and viral pathogens through various mechanisms including immunomodulation. Streptococcus pneumoniae endopeptidase O (PepO), a pneumococcal virulence protein, has been proven to enhance the phagocytosis of Staphylococcus aureus and Streptococcus pneumoniae by macrophages in our previous study, where we detected the down regulation of SH2 domain-containing inositol phosphatase 1 (SHIP1) and the up regulation of complement receptor 3 (CR3) in PepO-stimulated macrophages. In the present study, using SHIP1 over-expression plasmid and CR3 siRNA, we proved that the down regulation of SHIP1 and the up regulation of CR3 mediate the enhanced phagocytosis of S. aureus and S. pneumoniae by PepO-stimulated macrophages. The down regulation of SHIP1 also mediates the up regulation of CR3. To further determine whether PepO protects against respiratory pathogens, we constructed a mouse model with intranasal infection of S. aureus or S. pneumoniae and found that PepO significantly promoted their clearance. The down regulation of SHIP1 and the up regulation of CR3 also play a role in this process. This study provides a new preventive and therapeutic option for respiratory infectious diseases and lays the theoretical basis for the development of PepO as an immunomodulation agent.